Activation of indoleamine 2,3-dioxygenase in patients with scrub typhus and its role in growth restriction of Orientia tsutsugamushi. - Thanavadee Prachason; Kanittha Konhan; Piyapat Pongnarin; Somruedee Chatsiricharoenkul; Yupin Suputtamongkol; Chanin Limwongse (Public Library of Science (PLoS), 2012)
BACKGROUND: Our earlier genome-wide expression study revealed up-regulation of a tryptophan-catabolizing enzyme, indoleamine 2,3-dioxygenase (IDO1), in patients with scrub typhus. This gene has been previously reported to have anti-microbial activity in a variety of infectious diseases; therefore, we aimed to prove whether it is also involved in host defense against Orientia tsutsugamushi (OT) infection. METHODOLOGY/PRINCIPAL FINDINGS: Using LC-MS, we observed an increased ratio of serum L-kynurenine to serum L-tryptophan in patients with scrub typhus, which suggests an active catalytic function of this enzyme upon the illness. To evaluate the effect of IDO1 activation on OT infection, a human macrophage-like cell line THP-1 was used as a study model. Although transcription of IDO1 was induced by OT infection, its functional activity was not significantly enhanced unless the cells were pretreated with IFN-γ, a potent inducer of IDO1. When the degree of infection was evaluated by quantitative real-time PCR, the relative number of OT 47 kDa gene per host genes, or infection index, was markedly reduced by IFN-γ treatment as compared to the untreated cultures at five days post-infection. Inhibition of IDO1 activity in IFN-γ treated cultures by 1-methyl-L-tryptophan, a competitive inhibitor of IDO1, resulted in partial restoration of infection index; while excessive supplementation of L-tryptophan in IFN-γ treated cultures raised the index to an even higher level than that of the untreated ones. Altogether, these data implied that IDO1 was partly involved in restriction of OT growth caused by IFN-γ through deprivation of tryptophan. CONCLUSIONS/SIGNIFICANCE: Activation of IDO1 appeared to be a defensive mechanism downstream of IFN-γ that limited intracellular expansion of OT via tryptophan depletion. Our work provided not only the first link of in vivo activation of IDO1 and IFN-γ-mediated protection against OT infection but also highlighted the promise of this multifaceted gene in scrub typhus research.